The Role of Carbon in Sensory Protein Signal Transduction: Implications for Robotic Vision - Ekambaram, Rajasekaran; Rajasekaran, Devprakash; Rajasekaran, Indupriya; Rajasekaran, Meenal (Scientific Research, New Technologies and Applications Vol. 6, 2024)
This study applies the carbon code to predict the hydrophobic framework of retina-related proteins, focusing on carbon's role in proton absorption for signal transduction. Our results show that carbon frameworks in amino acid clusters within proteins are critical for forming optimized hydrophobic domains, influencing proton uptake into the cell core. In membrane-bound proteins involved in photon capture, specific amino acids regulate proton signaling and phototransduction. Mutations within these internal structures can significantly alter protein function, highlighting the importance of carbon-based frameworks and amino acid interactions in visual signal processing.